2019
DOI: 10.1111/1365-2656.13111
|View full text |Cite
|
Sign up to set email alerts
|

Ant diversity in Neotropical savannas: Hierarchical processes acting at multiple spatial scales

Abstract: Understanding what creates and maintains macroscale biodiversity gradients is a central focus of ecological and evolutionary research. Spatial patterns in diversity are driven by a hierarchy of factors operating at multiple scales. Historical and climatic factors drive large‐scale patterns of diversity by affecting the size of regional species pools, while habitat heterogeneity or microhabitat characteristics further influence species coexistence at small scales. We tested the degree to which the species–energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 73 publications
1
3
0
Order By: Relevance
“…Vegetation and habitat cover therefore appears to shape the distribution of ant species in Australia's temperate grassy woodlands over scales of only a few meters. This finding is congruent with other multiscale studies of ant communities that have identified important small-scale drivers of ant community structure (Maravalhas & Vasconcelos, 2020;Pérez-S anchez et al, 2023). Similar findings have been reported for arthropods and soil microbes in grassy woodlands (Barton et al, 2010(Barton et al, , 2017Hamonts et al, 2017).…”
Section: Habitat Effects Were Strongest At the Microhabitat Scalesupporting
confidence: 92%
See 1 more Smart Citation
“…Vegetation and habitat cover therefore appears to shape the distribution of ant species in Australia's temperate grassy woodlands over scales of only a few meters. This finding is congruent with other multiscale studies of ant communities that have identified important small-scale drivers of ant community structure (Maravalhas & Vasconcelos, 2020;Pérez-S anchez et al, 2023). Similar findings have been reported for arthropods and soil microbes in grassy woodlands (Barton et al, 2010(Barton et al, , 2017Hamonts et al, 2017).…”
Section: Habitat Effects Were Strongest At the Microhabitat Scalesupporting
confidence: 92%
“…Studies on animal communities, including ant communities (Cushman & McGarigal, 2002; Whittaker et al, 2001), have identified a hierarchical suite of factors affecting diversity and community composition, including large‐scale biogeographic factors like primary productivity down to small‐scale environmental heterogeneity and soil characteristics (Maravalhas & Vasconcelos, 2020; Pérez‐Sánchez et al, 2023; Spiesman & Cumming, 2008). Within this range of scales, vegetation or land use type can vary across landscapes, whereas vegetation cover or complexity can vary at much smaller, local scales (Oliver et al, 2016; Spiesman & Cumming, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, biogeographic patterns for regional biotas are sometimes necessarily inferred based on subsets of data. For instance, many biogeographic surveys have focused only on specific groups of organisms, such as birds (Hazzi et al, 2018), fish (Cowman et al, 2017), trees (Dick and Pennington, 2019), algae (Stekoll, 2019), crustaceans (Brun et al, 2020), or ants (Maravalhas and Vasconcelos, 2020), to name just a few. To some extent, however, different groups of organisms may differ in biogeographic pattern within a region, as the various drivers of species distribution may vary in importance among the groups (Qian et al, 1998;Hart and Chen, 2006;Chiu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between primary productivity and diversity has been demonstrated across taxonomic groups and spatial scales [1][2][3][4][5]. Primary productivity can be a fundamental driver of energy availability in a given system.…”
Section: Introductionmentioning
confidence: 99%